Объяснение:
По правилам Кирхгофа:
I₃ = I₁ + I₂
I₁R₁ - I₂R₂ = E₁ - E₂
I₃(R₃+R₄) - I₂R₂ = E₃ + E₄
Или:
5·I₁ - 10·I₂= 1 - 2
(12+4)·I₃ - 10·I₂ = 3 + 1
5·I₁ - 10·I₂= - 1
16·I₃ - 10·I₂ = 4
Решив систему, получаем:
I₁ = 0,18 A
I₂ = 0,19 A
I₃ = 0,37 А
U₁ = I₁·R₁ = 0,18·5 = 0,8 В
Объяснение:
По правилам Кирхгофа:
I₃ = I₁ + I₂
I₁R₁ - I₂R₂ = E₁ - E₂
I₃(R₃+R₄) - I₂R₂ = E₃ + E₄
Или:
I₃ = I₁ + I₂
5·I₁ - 10·I₂= 1 - 2
(12+4)·I₃ - 10·I₂ = 3 + 1
I₃ = I₁ + I₂
5·I₁ - 10·I₂= - 1
16·I₃ - 10·I₂ = 4
Решив систему, получаем:
I₁ = 0,18 A
I₂ = 0,19 A
I₃ = 0,37 А
U₁ = I₁·R₁ = 0,18·5 = 0,8 В